Molecular Composition of Dissolved Organic Matter in the Changjiang (Yangtze River) – Imprints of Anthropogenic Impact - Wu, Ying; Koch, Boris P.; Wang, Xiaona; Witt, Matthias; Wang, Xiaolu; Bao, Hongyan; Gan, Shuchai; Kattner, Gerhard; Zhang, Jing (Frontiers in Marine Science, 2022)
Understanding the biogeochemical transformation of dissolved organic matter (DOM) across fluvial networks will ultimately help to predict anthropogenic influences. To date, few studies have evaluated the anthropogenic impact on the spatial and temporal changes of DOM composition in large river systems. Here, FT-ICR-MS combined with excitation-emission matrix spectroscopy (EEMs) and biomarkers were applied to resolve chemical differences of DOM collected from the Changjiang basin at different hydrological and environmental conditions. PCA and cluster analysis illustrated that samples collected from lake systems and northern and southern tributaries differed from the two batches of main stream samples, particularly due to higher contribution of nitrogen and sulfur containing compounds. Correlation of land-use information along the tributaries with different PCA loadings indicated that agricultural, forest and wetland areas and wastewater discharge control the composition of DOM within these subregions. Higher heteroatom content (especially CHONx) in the low discharge period (2009) may be contributed by paddy soil leaching into groundwater. The relative peak magnitude of sulfur containing formulas was elevated during flood season (2010), which may be related to pollutions in areas of high population density. In addition, lignin phenol concentrations were higher in the flood season because of elevated soil erosion. Consequently, land use and human activities can strongly alter the quality and composition of DOM in watersheds flowing through densely populated regions, which may also impact the riverine carbon flux in anthropogenically disturbed river systems.